PENGENDALIAN PERSEDIAAN BAHAN BAKU TUMPI MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) DAN METODE PERIOD ORDER QUANTITY (POQ) DI UD. JAYA ABADI SOLUTION - Erik Suyanto, Andhika Mayasari, Nur Kholis (Universitas Hasyim Asy'ari, 2019)
The controlling planning of raw material needs in a company is very important to keep productivity on production activityand its influence on the material procurement cost. UD. Jaya Abadi Solution is one of the company that produces various fodder from the waste of animal feed manufacturing factory. The fluctuation often happens in raw material availability for production process especially â€œtumpiâ€ raw materialwhich causes the production process is not optimal. The purpose of the research is to control â€œtumpiâ€ raw material availability by using Economic Order Quantity (EOQ) method and Period Order Quantity (POQ) methodand to know the different cost between the company calculation and EOQ and POQ methods caculations. The methods used in this research are Economic Order Quantity (EOQ) method and Period Order Quantity (POQ) method, these methods are expected to be able to cope the fluctuation of the â€œtumpiâ€ raw material availability. Based on the result of the research using Economic Order Quantity (EOQ) method and Period Order Quantity (POQ) method yielded is EOQ value of 220 tons with total cost of Rp. 113.165.509, while POQ value is 205 tons with the total cost of Rp. 113.285.546. The different cost produced is 19 % compared to the company total cost.